The Usefulness of Mediastinal Cryobiopsy in the Diagnosis of Mediastinal Lymphadenopathy in HIV Patients - Sánchez-Cabral O; Osuna-Padilla IA; Majid A; Contreras-Garza BM; Negrete-García MF (HIV/AIDS: Research and Palliative Care)
Olivia Sánchez-Cabral,1 Iván Armando Osuna-Padilla,2 Adnan Majid,3 Belinda Maricela Contreras-Garza,1 María Fernanda Negrete-García1 1Interventional Pulmonology Unit, National Institute of Respiratory Diseases Ismael Cosío Villegas, Mexico City, Mexico; 2Clinical Nutrition Department, National Institute of Respiratory Diseases Ismael Cosío Villegas, Mexico City, Mexico; 3Interventional Pulmonology, Beth Israel Deaconess Medical Center, Boston, MA, USACorrespondence: María Fernanda Negrete-García, Email fernanda.negf@gmail.comIntroduction: Mediastinal diseases in HIV patients show complex diagnostic challenges due to opportunistic infections and rare neoplasms. While Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is a key technique, its effectiveness is limited as it only provides cytological samples. Endobronchial ultrasound-guided mediastinal cryobiopsy (CryoEBUS) emerges as a promising alternative, yielding larger and higher-quality samples. This study, the first in Mexico and the first worldwide in HIV patients, evaluates its diagnostic efficacy compared to EBUS-TBNA, highlighting its potential to improve disease management in immunocompromised populations.Materials and Methods: A prospective cross-sectional study has been conducted from April 2023 to October 2023 at a tertiary center for respiratory diseases in Mexico, evaluating the usefulness of the endobronchial ultrasound-guided mediastinal cryobiopsy (CryoEBUS) diagnostic in HIV-positive patients with mediastinal lymphadenopathy ≥ 1cm. Patients underwent CryoEBUS, with outcomes assessed via pathology and microbiology reports.Results: Eleven patients were included (64% male, mean age 39.1 years). CryoEBUS yielded diagnostic results in 82% of cases compared to 72% for bronchoalveolar lavage (BAL) and 50% for EBUS alone. Combined CryoEBUS and BAL demonstrated the highest yield (91%).Conclusion: In patients with HIV and mediastinal lymphadenopathy, mediastinal cryobiopsy has proven to be a useful, effective technique with a high diagnostic yield, especially for benign pathologies. It has also proven to be a safe technique and when combined with other lung sampling techniques, it improves the diagnostic yield of infectious diseases and rare neoplasms.Keywords: CryoEBUS, HIV, mediastinal disease, immunocompromised